Genotype, environment, seeding rate, and top‐dressed nitrogen effects on end‐use quality of modern Nebraska winter wheat. (27th June 2017) - Bhatta, Madhav; Regassa, Teshome; Rose, Devin J; Baenziger, P Stephen; Eskridge, Kent M; Santra, Dipak K; Poudel, Rachana
Abstract: BACKGROUND: Fine‐tuning production inputs such as seeding rate, nitrogen (N), and genotype may improve end‐use quality of hard red winter wheat ( Triticum aestivium L.) when growing conditions are unpredictable. Studies were conducted at the Agronomy Research Farm (ARF; Lincoln, NE, USA) and the High Plains Agricultural Laboratory (HPAL; Sidney, NE, USA) in 2014 and 2015 in Nebraska, USA, to determine the effects of genotype (6), environment (4), seeding rate (3), and flag leaf top‐dressed N (0 and 34 kg N ha −1 ) on the end‐use quality of winter wheat. RESULTS: End‐use quality traits were influenced by environment, genotype, seeding rate, top‐dressed N, and their interactions. Mixograph parameters had a strong correlation with grain volume weight and flour yield. Doubling the recommended seeding rate and N at the flag leaf stage increased grain protein content by 8.1% in 2014 and 1.5% in 2015 at ARF and 4.2% in 2014 and 8.4% in 2015 at HPAL. CONCLUSION: The key finding of this research is that increasing seeding rates up to double the current recommendations with N at the flag leaf stage improved most of the end‐use quality traits. This will have a significant effect on the premium for protein a farmer could receive when marketing wheat. © 2017 Society of Chemical Industry